Diseño geométrico y de pavimento flexible de la vía Paccha - Huacas - Santa Elena - Puente de Buza - ubicados en el cantón Atahualpa y Zaruma de la provincia de El Oro - Zapatanga Macas, Luis Enrique (2013)
The need for progress of peoples generates importance of communication channels as a way to build not only has the obligation joining two points , but also to bring development and progress to all areas that are incorporated into the new road system .